Efficacy Training As An Effort To Increase Employee Job Engagement In Review Of Employment Status - Sulastri; Soetjipto, Noer; Hidayat, Arif (The International Journal of Accounting and Business Society, 2022)
Purpose — This study aims to determine the influence of self-efficacy training on employees 'job engagement while distinguishing employees' job engagement based on employment status for employees of PT in a similar field of work. Telkomunikasi Indonesia, Tbk in Surabaya. Design/methodology/approach—The research method used was comparative studies, which were designed using experimental design techniques (experiments). Sampling was done through the cluster sampling technique, which involves taking two sample groups of employees. Research samples were taken from 60 respondents. Findings — This study indicates that the results of the independent t-test before being enforced on permanent and contract employees have a higher average job engagement value compared to permanent employees, with the same level of self-efficacy. After getting self-efficacy training employees, the value of T = -52.006 and P = 0,000 (p <0.05) prove the existence of significant changes in employee work involvement after obtaining efficacy training. For contract employees, the value of t = -56.542 and p = 0,000 (p <0.05) proves that employment contracts experience significant changes after receiving self-efficacy training for employees. The correlation coefficient value still explains that efficacy training is related to a work engagement of 74.8%, with a 56% effective contribution to job engagement. For employee contracts, the correlation coefficient value is 93.5%, which means the relationship between efficacy and work involvement is very strong, with the value of determination proving that the efficacy of 94.8% affects increasing the work involvement of contract employees. Practical implications—To improve employee job engagement, a company can hold efficacy training for both permanent and contract employees. Originality / Value—Efficacy Training Impacts or Influences Job Engagement, which is distinguished from employment status. Keywords — Efficacy Training, Job Engagement, Employment. Paper type — Research Paper